Pengaruh Teori Van Hiele Terhadap Pemahaman Konsep Matematika Materi Bangun Ruang Kubus Pada Siswa Kelas V SD Negeri 46 Pangkalpinang - Eka Oktavianti; Feri Ardiansah; Yudi Yunika Putra (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
The purpose of this research is to know the effect of Van Hiele theory to material the understanding of mathematical concepts in the cubes for the fifth grade students at SD Negeri 46 Pangkalpinag. The type of research for the used quantitative research using the experimental research method â€œpre experimental designâ€ (the one group pretest-postest design).The population in this research are the fifth grade students at SD Negeri 46 Pangkalpinang. The sampling technique used saturation sampling. The research sample are the fifth grade with totals 36 students. The data collection techniques in this research were in the form of questions, documentations and interviews. The data analysis techniques used the normally test, namely the liliefors test, and hypotesis testing using the related sample test in pairs with t-test. The result of this research shows that the Van Hiele theory influences the understanding mathematical concepts in the cube space material for the fifth grade students at SD Negeri 46 Pangkalpinang. This is based on the increased posttest result compared to the result of the pretest. In addition, the result of the hypotesis test are tcount: -4, 275 and ttable: 2, 028 based on criteria, tcount<ttable then Ha is acceptted tcount<ttable H0 is rejected. Based on the criteria on the hypotesis related curve for paired sampels namely if tcount is in the Ha acceptance area, the H0 is accepted, Ha is rejected. The result that there is the influence of Van Hiele theory to understanding mathematical concepts the cube space material for the grade students at SD Negeri 46 Pangkalpinang.